Origin of long-range ferromagnetic ordering in metal–organic frameworks with antiferromagnetic dimeric-Cu(II) building units - Göettlicher, Jörg (2013)
Even though metal–organic frameworks (MOFs) derived from antiferromagnetic dimeric-Cu(II) building units and nonmagnetic molecular linkers are known to exhibit unexpected ferromagnetic behavior, a comprehensive understanding of the underlying mechanism remains elusive. Using a combined theoretical and experimental approach, here we reveal the origin of the long-range ferromagnetic coupling in a series of MOFs, constructed from antiferromagnetic dimeric-Cu(II) building blocks. Our studies show that the strong localization of copper vacancy states favors spontaneous spin polarization and formation of local moment. These copper vacancy-induced moments are coupled via the itinerant electrons in the conjugated aromatic linkers to establish a long-range ferromagnetic ordering. The proposed mechanism is supported by direct experimental evidence of copper vacancies and the magnetic hysteresis (M-H) loops.